Optical Imaging Biomarkers of Drug-Induced Vascular Injury. Issue 1 (1st January 2015) - Lin, Shu-An; Suresch, Donna L.; Connolly, Brett; Mesfin, Gebre; Gonzalez, Raymond J.; Patel, Manishkumar R.; Shevell, Diane; Johnson, Timothy; Bednar, Bohumil
Drug-induced vascular injury (DIVI), defined as arterial medial degeneration/necrosis usually associated with perivascular inflammation, is frequently observed in the mesenteric arteries of rats but the relevance to humans remains a hurdle for drug development. Here, we describe the evaluation of commercially available optical imaging biomarkers using a rat DIVI model. Male Sprague Dawley rats were administered 10 mg/kg/day of a proprietary soluble guanylate cyclase activator (sGCa). Optical agents, AngioSense for the detection of vessel permeability, MMPSense for the detection of activated matrix metalloproteinases (MMPs), and IntegriSense for the detection of αv β3 integrin, were injected via tail vein 24 hours before fluorescence (FL) ex vivo imaging. Imaging found a statistically significant difference in FL from all optical agents between treated and vehicle groups (p < .05). Mesenteric arteries were further analyzed by histopathology, flow cytometry, and immunohistochemistry. Histopathology confirmed perivascular inflammation and/or arterial medial degeneration in the sGCa-treated animals. Flow cytometry of digested arteries revealed myeloid cells as a main source of MMPSense signal. Immunohistochemical analysis further identified elevated MMP-9 expression within arterial walls and surrounding tissue of treated animals. Together, these data demonstrate that MMPSense and AngioSense are sensitive optical imaging biomarkers for the quantification of DIVI in rat mesenteric arteries.